THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ORGANIZATIONAL COMMITMENT - Theng, Bestadrian P Theng; Susanto, Agus; Tanady, Darwan; Assaly, Arifin; Djakasaputra, Arifin (AGUSPATI Research Institute, 2021)
Employees are one of the important elements in every organization. Without employees, it will be difficult for organization to achieve their goal in this tight business competition. Based on the initial data that obtain in this research, it is know that there is a employees turnover every year in CV. Makmur Jaya Medan. One of the factors is due to employees in this company have a low emotional intelligence and can't commit in one organization for long term. Therefore, the problem of this research is to find